Time averaging for functional differential equations - Mustapha Lakrib (Journal of Applied Mathematics)
We present a result on the averaging for functional differential equations on finite time intervals. The result is formulated in both classical mathematics and nonstandard analysis; its proof uses some methods of nonstandard analysis.